Antusiasme dan Persepsi Peternak Lokal dalam Penyuluhan Budidaya Ayam Kampung Berbasis Teknologi Tepat Guna di Kabupaten Takalar - Agussalim, Agussalim; Mirnawati, Mirnawati; Napsawati, Napsawati; Muhiddin, St. Mutia Alfiyanti; Hatta, A. Afrinaramadhani (Program Studi Pendidikan IPA Fakultas MIPA Universitas Negeri Makassar, 2025)
The outreach activity on native chicken farming, incorporating the use of semi-intensive housing systems and locally sourced feed, was carried out to enhance the capacity of farmers in Bontomangape Village, Takalar Regency. This article focuses on examining participants’ enthusiasm and perceptions toward the appropriate technologies introduced. The extension methods used included material presentation, practical simulation, participatory discussion, and the distribution of evaluation and perception questionnaires. The results showed a high level of enthusiasm among participants, as reflected in full attendance, active engagement during sessions, and participation in hands-on practice. Overall, participants demonstrated strong enthusiasm and positive perceptions, as indicated by the questionnaire analysis: 90.6% strongly agreed that the outreach activity increased their enthusiasm, and 92.4% strongly agreed that the program elicited positive perceptions. These findings suggest that a participatory and context-based approach to agricultural extension can foster positive acceptance of farming innovations. Further follow-up in the form of mentoring and demonstration programs is needed to ensure sustainable technology adoption.